MOTIVASI BELAJAR PESERTA PELATIHAN TUTOR PELATIHAN JARAK JAUH (PJJ) KONSELOR HUMAN IMMUNO DEFICIENCY VIRUS (HIV) DI BALAI BESAR PELATIHAN KESEHATAN (BBPK) CILOTO - Amarullah, Rahmat Rizki (2014)
Distance training (PJJ) requires participants to learn independently (self directed learner), participation must arise of itself that considers the training is the solution to the problems faced, as well as distance training of HIV counselors who view HIV as a deadly disease that has no cure. One aspect that may affect the participants' learning motivation is a tutor, in this case the tutor must be highly motivated so that it can motivate the participants to learn. Problems that addressed in this study is about ) trainee's learning motivation of tutor training distance training (PJJ) counselor HIV at center for the training of health (BBPK) ciloto. The purpose of this study is to know : 1) The picture participants' perceptions of tutor training distance training of HIV counselor at center for the training of health (BBPK) Ciloto; 2) The picture participants' learning motivation of tutor training distance training of HIV counselor at center for the training of health (BBPK) Ciloto; 3) What are the factors intrinsic and extrinsic factors are the dominant learning motivation trainees of tutor training distance training of HIV counselor at center for the training of health (BBPK) Ciloto. Respondents are of tutor training distance training of HIV counselor at center for the training of health (BBPK) Ciloto many as 20 people. The method used in this research is a descriptive study using a quantitative approach. The research data collection tool using a questionnaire. This study uses concepts are : 1) Training concept, and; 2) Learning motivation concept. The results of this research found that : 1) The picture participants' perceptions of tutor training distance training of HIV counselor at center for the training of health (BBPK) Ciloto inferred well, trainees have a good perception of tutor training distance training of HIV counselor at center for the training of health (BBPK) Ciloto, views of the purpose of training, learning resources, teaching methods, learning facilities and learning environments that meet the expectations and in accordance with the needs of trainees; 2) The picture participants' learning motivation of tutor training distance training of HIV counselor at center for the training of health (BBPK) Ciloto inferred high, well intrinsic motivation that comes from are, the purpose of which has a goal of learning more than one main goal, which is in accordance with the interest of learning problems in the field, hope that can be a good tutor, learning readiness which encourages trainees learning, motivation comes from extrinsic source of learning is are participants positioned as adult learning, the methods used to encourage participants in the study, support learning facilities of learning process, and a conducive learning environment created during the activity; 3) The most dominating factor intrinsic learning motivation the trainees comes from the trainee learning objectives, and the most dominating factors extrinsic learning motivation the trainees come from a source of learning, and the most dominating learning motivation among the two is an intrinsic factor are the learning objectives the trainees themselves. Key word : Distance training (PJJ), HIV, Perceptions, and Learning Motivation Pelatihan Jarak Jauh (PJJ) menuntut pesertanya belajar secara mandiri (self directed learner), keikutsertaannya haruslah muncul dari dirinya sendiri yang menganggap pelatihan tersebut adalah solusi bagi masalah yang dihadapi, begitu pula dengan PJJ konselor HIV yang memandang virus HIV sebagai penyakit yang mematikan yang belum ada obatnya. Salah satu aspek yang dapat mempengaruhi motivasi belajar pesertanya adalah tutor, dalam hal ini tutor haruslah memiliki motivasi yang tinggi sehingga dapat menumbuhkan motivasi belajar pesertanya. Masalah yang dibahas dalam penelitian ini adalah mengenai motivasi belajar peserta pelatihan tutor pelatihan jarak jauh (PJJ) konselor HIV di Balai Besar Pelatihan Kesehatan (BBPK) Ciloto. Tujuan dari penelitian ini adalah untuk mengetahui : 1) Gambaran persepsi peserta pelatihan tutor PJJ konselor HIV di Balai Besar Pelatihan Kesehatan (BBPK) Ciloto; 2) Gambaran motivasi belajar peserta pelatihan tutor PJJ konselor HIV di Balai Besar Pelatihan Kesehatan (BBPK) Ciloto; 3) Apa saja faktor intrinsik, dan faktor ekstrinsik yang memdominasi motivasi belajar peserta pelatihan tutor PJJ konselor HIV di Balai Besar Pelatihan Kesehatan (BBPK) Ciloto. Responden penelitian ini adalah peserta pelatihan tutor PJJ konselor HIV di Balai Besar Pelatihan Kesehatan (BBPK) Ciloto sebanyak 20 orang. Metode yang digunakan dalam penelitian ini adalah metode penelitian deskriptif dengan menggunakan pendekatan kuantitatif. Alat pengumpul data penelitian menggunakan angket. Penelitian ini menggunakan konsep-konsep yaitu : 1) Konsep Pelatihan, dan; 2) Konsep Motivasi Belajar. Hasil penelitian ini ditemukan bahwa : 1) Gambaran persepsi peserta pelatihan terhadap pelatihan tutor PJJ konselor HIV di Balai Besar Pelatihan Kesehatan (BBPK) Ciloto disimpulkan baik, peserta pelatihan memiliki persepsi yang baik terhadap pelatihan tutor PJJ konselor HIV BBPK Ciloto, dilihat dari tujuan pelatihan, sumber belajar, metode belajar, sarana dan prasarana belajar, dan lingkungan belajarnya yang memenuhi harapan dan sesuai dengan kebutuhan peserta pelatihan; 2) Motivasi belajar peserta pelatihan tutor PJJ konselor HIV di Balai Besar Pelatihan Kesehatan (BBPK) Ciloto disimpulkan tinggi, baik motivasi yang berasal dari intrinsiknya yaitu, tujuan belajarnya yang memiliki tujuan lebih dari satu tujuan utama, minat belajarnya yang sesuai dengan masalah di lapangan, harapannya agar dapat menjadi tutor yang baik, kesiapan belajarnya yang medorong peserta pelatihan lebih giat belajar, motivasi yang berasal dari ekstrinsiknya adalah yaitu sumber belajar yang memposisikan peserta sebagai orang dewasa yang belajar, metode yang digunakan mampu mendorong peserta dalam belajar, sarana dan prasanara belajar menunjang proses belajar, dan lingkungan belajar yang kondusif tercipta selama kegiatan berlangsung; 3) Faktor intrinsik yang paling mendominasi motivasi belajar peserta pelatihan berasal dari tujuan belajar peserta pelatihan, dan faktor ekstrinsik yang paling mendominasi motivasi belajar peserta pelatihan berasal dari sumber belajar , dan yang paling mendominasi motivasi belajar diantara keduanya adalah faktor intrinsik yaitu tujuan belajar peserta pelatihan itu sendiri. Kata kunci : Pelatihan Jarak Jauh (PJJ), HIV, Persepsi, dan Motivasi Belajar.